Multi-Component-Multiphase Flash Calculations for Systems Containing Gas Hydrates by Direct Minimization of Gibbs Free Energy - Amir Abbas Izadpanah; Mohsen Vafaie Sefti; Farshad Varaminian (Iranian Journal of Chemistry & Chemical Engineering, 2006)
The Michelsen stability and multiphase flash calculation by direct minimization of Gibbs free energy of the system at constant temperature and pressure, was used for systems containing gas hydrates. The solid hydrate phase was treated as a solid solution. The fugacities of all components of the hydrate phase were calculated as a function of compositions by the rearranged model of van der Waals and Platteeuw. Using this rearranged model enables the use of multiphase flash algorithm for systems containing gas hydrates. Based on this calculation for hydrate phases, we can determine amounts of hydrate formed and structure stability based on a minimum Gibbs free energy criterion.